Routine Stock Opname in Enhancing Service of Halodoc's Order and Increasing Transactions - I Nyoman Arya Purnata Megantara; Titien Siwi Hartayu (Sanata Dharma University, 2025)
In partnering with the e-commerce platform Halodoc, one of the challenges encountered is unfulfilled orders due to discrepancies between the system's stock and conventional stock. Therefore, the researcher aims to determine whether maintaining drug availability through routine stock opname in an online (e-commerce) setting can also enhance service quality. This study is quasi-experimental research conducted at Manut Farma Pharmacy from July to September 2023. The research involves daily routine stock opname of 312 registered drug items on the Halodoc application. These 312 drug items met the inclusion criteria, which were